Evaluation of cell proliferation and endometrial thickness of bitches in different periods of diestrus - GOSSLER,VANESSA S.A. (2017)
ABSTRACT This study aimed to determine the histological features of the endometrium of bitches, as well as the cell proliferation at specific moments of diestrus, 10, 20, 30, 40, 50 and 60 days post ovulation, correlating the endometrial thickness with the uterine cell proliferation and the metabolic state (weight, blood glucose and plasma cholesterol) of the animals. Therefore, the right and left uterine horns of 26 clinically healthy bitches submitted to ovariohysterectomy were histologically analyzed 10, 20, 30, 40, 50 and 60 days post ovulation. The hematoxylin-eosin and AgNOR staining techniques were performed. All parameters were evaluated by ANOVA and post-hoc Tukey test (p<0.05). The correlation between endometrial thickness and uterine cell proliferation, weight, blood glucose and plasma cholesterol of animals was observed using the Pearson method (p<0.05). In the present study, it is concluded that endometrial thickness does not differ at any of the moments analyzed in diestrus. The endometrial thickness is not influenced by hormones, weight, blood glucose or serum cholesterol of bitches in this phase of the estrous cycle. However, there is greater cell proliferation in the endometrium at day 40 compared to day 60 post ovulation under the influence of the endocrine profile.